Learning about self: leadership skills for public health - Rob Moodie (Journal of Public Health Research, 2016)
As public health practitioners and as clinicians we are taught to care for our patients, and for our community members. But how much do we teach and learn about how to lead, manage and care for our colleagues, our team members and ourselves? This paper emphasizes the need for leadership learning and teaching to become an essential element of the practice of public health. The paper presents the author’s perspective on the leadership skills required for public health and describes a five-day intensive course designed to enable participants to develop these skills over time. The paper briefly covers leadership definitions, styles and types and key leadership skills. It mainly focuses on the design and ethos of the course, skills self-assessment, group interaction and methods for developing and refining leadership skills. The course uses a collaborative learning approach where the power differential between teachers, facilitators, guests and participants is minimized. It is based on creating an environment where any participant can reveal his or her stories, successes, failures, preferences and dislikes in a safe manner. It encourages continual, constructive individual reflection, self-assessment and group interaction. The course is aimed at the practice of public health leadership, with a particular emphasis on the leadership of self, of knowing oneself, and of knowing and understanding colleagues retrospectively as well as prospectively. The most important outcome is the design and implementation of participants’ own plans for developing and nurturing their leadership skills.